Le libre-échange avec les États-Unis - Parizeau, Jacques (Assurances, 1986)
The author gives an overview of the free trade-proposal between the United States and Canada and, taking the province of Quebec in particular, concludes thus: "Will anything ever come of the negotiations? Or do we have to be content with limited free trade? Will whole areas of trade be left out of the agreement? Worse still, will we fail completely? lt is still too early to say. lt does seem clear, however, that Quebec has much more to gain than to lose from a free-trade agreement with the United States. Favouring such an exchange are the recent upswing of business in Quebec, the rapid pace of current technological advances, improved funding and the ability to adapt to these changes.